A comparative study of two Mississippian dolostone reservoirs in the Volga-Ural Basin, Russia. (1st September 2020) - Kolchugin, Anton; Immenhauser, Adrian; Morozov, Vladimir; Walter, Benjamin; Eskin, Aleksey; Korolev, Eduard; Neuser, Rolf
Graphical abstract: Highlights: Contrast-comparison of dolostones located on flanks and crests of anticlinal hydrocarbon reservoirs. Petrographic, isotopic and fluid inclusion data set provides evidence of coeval formation of burial dolostone. Replacive and porosity-destructive dolomitization has deteriorated reservoir properties. The temperature range, as based on fluid-inclusion data, points to an abnormally high-temperature background thermal regime in the Volga-Ural basin. Abstract: A significant proportion of the remaining oil reserves worldwide is concentrated in dolostone rock bodies. The present paper focuses on Tournaisian and Visean limestones and geologically younger diagenetic dolomite units in two mature oil fields of the Volga-Ural Basin, Russia. In contrast to many dolostone-hosted hydrocarbon reservoirs worldwide, the Tournaisian and Visean dolostones in the Demkinskoye and the Onbiyskoye oil fields plot near the low end of the porosity–permeability range. Replacive and porosity-destructive burial dolomitization has deteriorated the reservoir properties of these units. Dolomitization is related to the ascent of hot (170–215 °C) and saline (22–24 wt%) fluids as based on fluid inclusion data. This temperature range points to an abnormally high temperature background thermal regime of the Volga-Ural basin. The onset of burial dolomitization predates oil charge as documented by the fact that oil-bearing inclusions are only present in the outermost zones of porosity-occluding dolomite cements. Isotope geochemical data, dolomite petrography and fluid inclusion data reveal important similarities between hydrothermal dolostone units in the Demkinskoye and the Onbiyskoye oil fields. Based on these data and the detailed cement stratigraphy presented here, it is argued that dolomite bodies in both oil fields formed as the result of one main, Alpine tectonic event pushing hot and saline dolomitizing brines ahead of ascending hydrocarbons.